Empowerment of Religious Values in Controlling Divorce Rates in Parepare City (Analysis of the Role of Religious Institutions) - Mulki Sahnur; Agus Muchsin; Rusdaya Basri; M. Nasri Hamang; Zainal Said (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The aim of this research is to describe the factors that influence the high divorce rate in Parepare City. Next, it provides an analysis of religious relations in response to the high divorce rate and the role of religious institutions in minimizing the occurrence of divorce in Parepare City. This research is a type of qualitative descriptive research with a field research style with a phenomenological approach which is useful for exploring the factors that influence the high divorce rate in Parepare City as well as religious relations and the role of religious institutions in minimizing the divorce rate in Parepare City. The primary data source for this research was obtained from direct interviews with religious institutions in Parepare City. The research results show: 1). Several factors for the high divorce rate in Parepare City are due to domestic violence, then other factors are also due to a person's level of education in married life, and the factor of not fulfilling a living both physically and mentally and a factor in the occurrence of divorce is a person's low religious values. 2). Divorce law is something that requires clear causes and conditions regarding the time the divorce occurred. Because if a divorce is carried out without any particular reason and without paying attention to the conditions or time of the divorce, the divorce may not be carried out. Divorce from a religious perspective is something that can definitely happen as a result of marriage, but divorce is the thing that is most hated by Allah and His Messenger. 3). The role of religious institutions in Parepare City in reducing the high divorce rate is by optimizing the function of the BP4 institution which plays a role as an educational, consultative and marriage empowerment institution. Apart from that, the BP4 institution also provides competent staff such as expert advisors and religious instructors who are expected to be able to carry out their roles in broadcasting religious messages in accordance with the beliefs of those they train.